Harnessing Copper's Potential: A Review of Cu-Based Catalysts for Glycerol Conversion - Ahmed, Sabeel; Abdullah, Iman; Krisnandi, Yuni Krisyuningsih (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The increasing depletion of fossil fuel reserves and environmental concerns have accelerated the search for sustainable alternatives, leading to the utilization of biodiesel as a renewable energy source. Glycerol, a key byproduct of biodiesel production, has been extensively investigated for conversion into value-added compounds such as lactic acid, acrylic acid, and 1,2-propanediol (1,2-PDO). Copper-based catalysts have gained popularity due to their low cost, high catalytic efficiency, and environmental friendliness. This review examines various copper-based catalytic systems for glycerol conversion through key processes such as hydrogenolysis, oxidation, steam reforming, and dehydration. The work focuses on how Cu-based bimetallic catalysts, such as Cu-Ni, Cu-Co, and Cu-Zn, improve reaction selectivity and conversion rates via synergistic interactions, better metal dispersion, and optimized redox properties. Furthermore, new catalyst manufacturing methods, such as ammonia evaporation, hydrothermal, and ion exchange approaches, have shown improved stability and reusability. The findings show that Cu-based catalysts successfully facilitate high glycerol conversion, with selective pathways favouring the generation of 1,2-PDO, lactic acid, and acrylic acid under optimal circumstances. However, catalyst deactivation caused by sintering and coke formation remains a concern. Future research should concentrate on creating stable, multifunctional catalysts, adding bio-derived support, and improving reaction conditions to increase long-term efficiency and industrial usability. This review emphasizes the potential of Cu-based catalytic systems in promoting glycerol valorisation and achieving a more sustainable chemical industry. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).